2005
DOI: 10.3923/ijps.2005.900.904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ascorbic Acid and Acetylsalicylic Acid Supplementation on Performance of Broiler Chicks Exposed to Heat Stress

Abstract: A total of 100, day-old broiler chickens were randomly divided into 5 groups and kept under elevated temperature (34-36EC) to see the effect of ascorbic acid and acetylsalicylic acid (Sb-Asper-C, a commercial product) on the feed conversion ratio (FCR), immune status and ratio of weight of bursa, thymus and spleen to body weight. Heat stress increased the FCR but decreased the immune response and ratio of bursa, thymus and spleen to body weight of the birds. Ascorbic acid and acetylsalicylic acid supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…To compare the resulting biological activities not only versus a control diet but also versus a well-known immunostimulant and antioxidant substance, the experimental plan also included the administration of AA in the diet, nowadays one of the substances employed to enrich diets mainly when animals are exposed to environmental stressors. In fact, if the effect of dietary AA supplementation in poultry is well known (Naseem et al 2005;Asli et al 2007;Mirfendereski and Jahanian 2015), less information is available on the potential use of medicinal plants or phytobiotics in which active compounds are secondary plant constituents (Hajati et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To compare the resulting biological activities not only versus a control diet but also versus a well-known immunostimulant and antioxidant substance, the experimental plan also included the administration of AA in the diet, nowadays one of the substances employed to enrich diets mainly when animals are exposed to environmental stressors. In fact, if the effect of dietary AA supplementation in poultry is well known (Naseem et al 2005;Asli et al 2007;Mirfendereski and Jahanian 2015), less information is available on the potential use of medicinal plants or phytobiotics in which active compounds are secondary plant constituents (Hajati et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Ferket and Qureshi (1992) on the efficacy of different vitamins and electrolyte treatments in drinking water for heat-stressed broilers, the authors observed that vitamin C treatment increased body weight gain and feed conversion by 3 and 5%, respectively and reduced the rate of HS induced death by 63%. In addition, dietary vitamin C supplementation for HS-challenged broiler chicks positively affected the relative weights and immune status of bursa, thymus, and spleen (Naseem et al, 2005). Also, supplementation of vitamin C at 200 ppm was shown to be beneficial for improving weight gains, nutrient digestibility, carcass traits, and bone resistance and helped to reach the full genetic potential of commercial broilers (Lohakare et al, 2005).…”
Section: Vitamin Cmentioning
confidence: 98%